Jesús de Nazaret. Segunda parte, Desde la entrada en Jerusalén hasta la Resurrección - Benedict XVI, Pope, 1927-; Río, J. Fernando P. del‏ (Madrid : Encuentro, 2011)
In his first book written as pope, Benedict XVI offers a portrait of Jesus based on the Gospels and encourages Christians to better understand the central figure of their faith.
Includes bibliographical references and index.
Online resource; title from PDF title page (Digitalia, viewed August 29, 2016)
Keywords: Jesus Christ -- Biography; Jesus Christ -- Person and offices; Jesus Christ -- Historicity; Holy Week; Jesus Christ; Bible; Electronic books